A neurological and philosophical perspective on the design of environments and technology for older people with dementia. Issue 2 (25th June 2018) - Verkerk, Maarten J.; van Hoof, Joost; Aarts, Sil; de Koning, Sylvia J.M.M.; van der Plaats, Johanna J.
Abstract : Purpose: Older people with dementia (OPD) have specific housing and technology-related needs, for which various design principles exist. A model for designing environments and its constituting items for people with dementia that has a firm foundation in neurology may help guide designers in making design choices. The paper aims to discuss these issues. Design/methodology/approach: A general design model is presented consisting of three principles for OPD, namely designing for ageing people; designing for a favourable state and designing for beautiful moments. The neurosciences as a whole give shape to an eminent framework explaining the behaviour of OPD. One of the objectives of this paper is to translate the design principles into design specifications and to show that these specifications can be translated in a design. Findings: Philosophical concepts are introduced which are required to understand design for OPD. Four case studies from Dutch nursing homes are presented that show how the theory of modal aspects of the philosopher Dooyeweerd can be used to map design specifications in a systematic way. Research limitations/implications: These examples of design solutions illustrate the applicability of the model developed in this article. It emphasises the importance of the environment for supporting the daily life of OPD. Originality/value: There is a need for a design model for OPD. The environment and technology should initiate positive behaviours and meaningful experiences. In this paper, a general model for the designing of environments for OPD was developed that has a firm foundation in neurology and behavioural sciences. This model consists of six distinct steps and each step can be investigated empirically. In other words, this model may lay the foundation for an evidence-based design.